Risiko Online Pada Remaja dan Pendidikan Literasi Media Baru - Amia Luthfia (Postgraduate of Jayabaya University, 2016)
Teenager aged 10-19 years is the digital native generation and thetj are connected with the virtual world almost every time. Online activities they do, among others, are connected through social media, search for information on various websites, downloading music, watching movies via YouTube, read the news, play on-line games, and etc. Teens' on-line activity behind it has a variety of risks and should be examined together with any kind of on-line risks experienced by adolescents as a first step in order to minimize the negative effects that rcould occur. This article contains a study of the conceptualization of on-line risk, scope and classification of on-line risk; featuring a wide range of research011 the influence of social environment on the risk of on-line teens; and attempts to deal with the risk of negative media that hit young people through new media literacy education. Media literacy curriculum that already exist.>hould be adapted to the characteristics of new media. At its core, the new media literacy should include: (1) media literacy; (2) d igital technologtj literacy; (3) civil and social respol?sibility; and ( 4) imagination and creativih;.